The Neurological Pupil index for outcome prognostication in people with acute brain injury (ORANGE): a prospective, observational, multicentre cohort study - Oddo, Mauro; Taccone, Fabio S.; Petrosino, Matteo; Badenes, Rafael; Blandino-Ortiz, Aaron; Bouzat, Pierre; Caricato, Anselmo; Chesnut, Randall M.; Feyling, Anders C.; Ben-Hamouda, Nawfel; Hemphill, J. Claude; Köhn, Julia; et al. (Lancet Neurology, 2023)
Background: Improving the prognostication of acute brain injury is a key element of critical care. Standard assessment includes pupillary light reactivity testing with a hand-held light source, but findings are interpreted subjectively; automated pupillometry might be more precise and reproducible. We aimed to assess the association of the Neurological Pupil index (NPi)—a quantitative measure of pupillary reactivity computed by automated pupillometry—with outcomes of patients with severe non-anoxic acute brain injury. Methods: ORANGE is a multicentre, prospective, observational cohort study at 13 hospitals in eight countries in Europe and North America. Patients admitted to the intensive care unit after traumatic brain injury, aneurysmal subarachnoid haemorrhage, or intracerebral haemorrhage were eligible for the study. Patients underwent automated infrared pupillometry assessment every 4 h during the first 7 days after admission to compute NPi, with values ranging from 0 to 5 (with abnormal NPi being <3). The co-primary outcomes of the study were neurological outcome (assessed with the extended Glasgow Outcome Scale [GOSE]) and mortality at 6 months. We used logistic regression to model the association between NPi and poor neurological outcome (GOSE ≤4) at 6 months and Cox regression to model the relation of NPi with 6-month mortality. This study is registered with ClinicalTrials.gov, NCT04490005. Findings: Between Nov 1, 2020, and May 3, 2022, 514 patients (224 with traumatic brain injury, 139 with aneurysmal subarachnoid haemorrhage, and 151 with intracerebral haemorrhage) were enrolled. The median age of patients was 61 years (IQR 46–71), and the median Glasgow Coma Scale score on admission was 8 (5–11). 40 071 NPi measurements were taken (median 40 per patient [20–50]). The 6-month outcome was assessed in 497 (97%) patients, of whom 160 (32%) patients died, and 241 (47%) patients had at least one recording of abnormal NPi, which was associated with poor neurological outcome (for each 10% increase in the frequency of abnormal NPi, adjusted odds ratio 1·42 [95% CI 1·27–1·64]; p<0·0001) and in-hospital mortality (adjusted hazard ratio 5·58 [95% CI 3·92–7·95]; p<0·0001). Interpretation: NPi has clinically and statistically significant prognostic value for neurological outcome and mortality after acute brain injury. Simple, automatic, repeat automated pupillometry assessment could improve the continuous monitoring of disease progression and the dynamics of outcome prediction at the bedside. Funding: NeurOptics.
CRIS-Team Scopus Importer:2023-09-29